Procesos contables de la Empresa Stratum Global & Associatescom S.A. del cantón Babahoyo en el periodo 2023. - Macias Calvache, Bianka Anabella (2024)
The present case study entitled: “Accounting processes of the company Stratum Global & Associatescom s.a. of the Babahoyo canton in the period 2023”, has as general objective to analyze the accounting processes of the company, through the verification of the accounting information, carrying out a research methodology with a mixed quantitative and qualitative approach with interview and observation techniques; Therefore, for the elaboration of the subject to investigate, the research line determined as “Financial, Administrative, Tax, Audit and Control Management” and the sub-line “Financial, Tax and Social Commitment Management” is established, which is relevant as a starting point in the influence of the accounting processes of the company. In the results, the accounting procedures were diagnosed, an observation guide and a respective questionnaire with some questions to the accounting personnel, identifying deficiencies in the accounting processes of the company; in addition, the impact of these processes in the decision making and transparency was shown, through a respective analysis of the financial statements. To conclude this summary, conclusions and recommendations were also elaborated to understand if the organization is adequately complying with its accounting processes, through the review of documents and accounting policies, to establish possible areas for improvement.